Malaysian household debts in relation to macroeconomic factors / Nur Syafiqah Noor Azmi - Noor Azmi, Nur Syafiqah (2019)
The spike in Malaysia's household debts has caused stoked tensions as it has nearly reached 82.2% of total GDP. The amount of household debts, as it may cause another financial crisis is considered to be troubling. The purpose of this study is to analyse factors that influence household debts in Malaysia via time series data. This study employs multiple linear regression method and the macroeconomic variables used consist of housing prices, household income, and population growth as independent variables taken in the period from 2002 to 2019. The results show that the population growth is the most significance variable, followed by household income and housing prices. Population growth and household income would have a positive impact on household debts, indicating that the increase in household debts is dictated by the increase in these explanatory variables. However, housing prices would exert a negative influence on the rise of household debts. Findings of this study could provide some guidance to policymakers in controlling the mounting debt level and help in realizing the nation economic goals